A comprehensive cross-sectional study on the current status of proactive health awareness among Guangxi healthcare workers and its influencing factors: understanding from both individual and variable viewpoints - Chen, Wuzhao; Guan, Qinyi (Frontiers in Public Health, 2025)
BackgroundEnhancing awareness of proactive health concepts among healthcare professionals is vital in the context of an aging population and limited resources, shifting the focus from “patients and diseases” to “individuals and health.”MethodsUsing a self-developed Health Action Survey Questionnaire, this study assessed the proactive health cognition of randomly selected healthcare providers in Guangxi Zhuang Autonomous Region. Analyses included latent class models, binary logistic regression, and mediation effects.ResultsAmong 173,892 participants, 77,307 (44.46%) were unaware of proactive health. Significant differences in health behaviors cognition and willingness to disseminate health knowledge identified 4 groups among healthcare staff. Those with low health action cognition were more likely to know about proactive health, while those with high cognition and willingness had lower awareness. Health action cognition and willingness also indirectly influenced awareness through satisfaction with government health initiatives.ConclusionVariations in health action cognition and willingness among Guangxi healthcare staff impact their awareness of proactive health. Relevant departments should prioritize healthcare workers who demonstrate both high awareness of the “Healthy China Action (2019–2030)” and the “Healthy Guangxi 2030” plan and a strong willingness to engage in health-science popularization, focusing on enhancing their satisfaction with government health initiatives to improve public-health outcomes.